INOVASI ATAU STAGNASI? PENGARUH DISRUPSI TEKNOLOGI INFORMASI TERHADAP EFISIENSI PENGELOLAAN KEUANGAN PUBLIK DI SULAWESI UTARA - Lakat, Junior Semuel; Kumenaung, Anderson Guntur; Lengkong, Victor Paskah Kalawat; Gamaliel, Hendrik (ANALISIS, 2025)
The background of this research focuses on the rapid development of information technology that has transformed various sectors, including public financial management. In North Sulawesi, the implementation of information technology in financial management is expected to enhance transparency, accountability, and efficiency. However, challenges such as inadequate infrastructure and limited human resource capacity may hinder effective implementation. The objective of this study is to evaluate the impact of information technology disruption on the efficiency of public financial management in North Sulawesi. The method employed is a quantitative approach with descriptive-analytical analysis, involving data collection from technology-based systems such as e-budgeting, SIPKD, and cloud-based financial management systems. The results indicate that the implementation of information technology significantly improves efficiency, transparency, and accountability in public financial management. Nevertheless, challenges related to infrastructure and human resource capacity remain obstacles to achieving optimal results. The conclusion of this research is that information technology disruption has great potential to enhance public financial management, but greater attention is needed towards infrastructure development and human resource training to ensure successful implementation.